2012
DOI: 10.1073/pnas.1200952109
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of unconscious contextual effects in orientation processing

Abstract: Contextual effects abound in the real world; how we perceive an object depends on what surrounds it. A classic example of this is the tilt illusion (TI) whereby the presence of a surround shifts the perceived orientation of a target. Surprisingly, the magnitude and direction of this shift depend on the orientation difference between the target and surround: when their orientations are similar, the perceived difference is amplified and the target appears repelled in orientation from the surround (i.e., the TI).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 45 publications
5
27
2
Order By: Relevance
“…In a recent paper by Mareschal and Clifford (2012), the authors suggested that a single mechanism operating in the early stages of visual processing (before conscious perception of the surround) could account for both the tilt repulsion and attraction. They used a reversecorrelation technique, in which the surround orientation was changed every 12 ms making it invisible to observers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent paper by Mareschal and Clifford (2012), the authors suggested that a single mechanism operating in the early stages of visual processing (before conscious perception of the surround) could account for both the tilt repulsion and attraction. They used a reversecorrelation technique, in which the surround orientation was changed every 12 ms making it invisible to observers.…”
Section: Discussionmentioning
confidence: 98%
“…In order to demonstrate different mechanisms or explore the level of segmentation information processing, a backward noise masking of the surround (Clifford & Harris, 2005) or a rapid reverse-correlation method (Mareschal & Clifford, 2012) could be useful. In a recent paper by Mareschal and Clifford (2012), the authors suggested that a single mechanism operating in the early stages of visual processing (before conscious perception of the surround) could account for both the tilt repulsion and attraction.…”
Section: Discussionmentioning
confidence: 99%
“…Perceptual integration ensured that the rapid succession of surround gratings effectively masked one another so that observers were at all times blind to their orientation. Mareschal and Clifford (2012) nonetheless found that direct and indirect tilt illusions occurred reliably and over a similar time course, implicating a single mechanism operating in the early stages of visual processing before conscious extraction of the surround orientation.…”
Section: Does the Tilt Illusion Require Awareness Of The Surround Orimentioning
confidence: 91%
“…The influence of the surround declines with distance from the test (Mareschal & Clifford, 2013;Virsu & Taskinen, 1975). Repulsive and attractive effects do not require awareness of the surround orientation (Mareschal & Clifford, 2012) and are observed not only for orientation defined by (first-order) modulations in luminance but also for (second-order) contrast modulations (Smith, Clifford, & Wenderoth, 2001;Wenderoth, Clifford, & Ma Wyatt, 2001) and purely chromatic modulations (Clifford et al, 2003a(Clifford et al, , 2003b.…”
Section: Introduction: Basic Phenomenology and Early Ideasmentioning
confidence: 94%
See 1 more Smart Citation